IMPROVING NARRATIVE WRITING SKILLS USING COOPERATIVE THINK, WRITE AND TALK (TWT) IN CLASS IX-1 SMP NEGERI 2 MUARA FY 2018/2019 - Simanullang, Rindawati (Jurnal Sabilarrasyad, 2020)
The problem in this research is the students' low skill in writing narrative essays. This study aims to determine whether narrative writing skills can be improved by using Think Write and Talk (TWT) in Indonesian language lessons with basic writing competencies in Class IX-1 SMP Negeri 2 Muara TA 2018/2019. The type of research used in this research is classroom action research. The subjects in this study were all students of Class IX-1 SMP Negeri 2 Muara TA 2018/2019, totaling 32 students. The object of narrative essay writing skills, while the learning action uses the Think Write and Talk (TWT) model as a teacher's effort to improve students' narrative writing skills. Data collection techniques used tests and observations. Based on the data found at the time of the pretest, out of 32 students, 6 students obtained a classical completeness level of 18.75% who got a complete score with a KKM value of 70, and as many as 26 students 81.25% got an incomplete score with an average score of 46, 25. In the first cycle, there were 15 students 46.88% got a complete score, and as many as 17 students 53.22% received an incomplete score with an average score of 60.78. In the second cycle, the classical completeness level was obtained as many as 29 students 90.63% who got complete scores, and as many as 3 students 8.37% who completed with an average score of 81.41. Thus, it can be concluded that the use of Think Write and Talk (TWT) can improve narrative writing skills in Class IX-1 SMP Negeri 2 Muara, TA 2018/2019. Therefore, teachers need to improve their teaching skills, especially by using Think Write and Talk (TWT) cooperative learning.